Towards designing de novo (1--->4)-linked polysaccharides - Chen, Jeff Yu-Jen (Department of Chemistry, 2024)
Carbohydrates are invaluable in a variety of industrial applications ranging from biodegradable materials to pharmaceutical drug carriers. Small functional groups, such as hydroxyl, amine, N-acetylamide and methoxy are commonly employed for creating de novo saccharides with enhanced functionality. The physiochemical properties of carbohydrates are governed by their conformations and the polarity of their substituents strongly influences the overall flexibility of such biomolecules. In this thesis, two types of (1--->4)-inter-glycosidic interactions, viz. hydrogen bonding and hydrophobic effects, are investigated.